Sustainable Internationalization In Higher Education: Exploring Institutional Perceptions On Low-Carbon Mobility Practices At ITB - Nuril Aisyah Auliani; Andika Putra Pratama (Yayasan Riset dan Pengembangan Intelektual, 2026)
The process of internationalization of higher education institutions is increasingly being threatened by the need to address issues of sustainability, especially those related to academic mobility. The main aim of the research is to explore how sustainability is understood, limited, and implemented within the internationalization process of Institut Teknologi Bandung (ITB) in Indonesia. To achieve the research aims, a qualitative phenomenological research design will be employed to collect data through semi-structured interviews with key individuals at ITB involved in the process of internationalization. The research will be guided by various theoretical models such as institutional theory, organizational change and learning, systems theory, and collaborative governance. The research established that the process of internationalization at ITB is still largely dependent on physical mobility, which has a huge impact on its carbon footprint. Sustainability has been poorly integrated into the process of decision-making related to mobility. External drivers such as ranking and country policies have dominated the sustainability agenda at ITB. Structural limitations such as rigid curriculum models, bureaucratic hurdles, inadequate digital technologies, and lack of carbon tracking have limited the adoption of low-carbon mobility at ITB. The proposed strategic framework aims to integrate sustainability into internationalization by focusing on diversification of mobility modalities, governance integration, curriculum change, capacity building, and carbon accountability. The current research contributes to the existing literature on internationalization by providing new knowledge from the Global South, as well as recommendations to ensure global competitiveness while being climate responsible, and to support the global effort to decarbonize academic mobility.